Descriptive analysis of trends in frequency of Invalidity Pension Scheme (IPS) in Malaysia / Mohd Zaki Awang Chek, I. L. Ismail and Nur Faezah Jamal - Awang Chek, Mohd Zaki; Ismail, I. L.; Jamal, Nur Faezah (Universiti Teknologi MARA, Perak, 2018)
Social insurance was introduced in Malaysia in 1971 through Social Security Organisation (SOCSO). Herein, we describe the increasing trend number of SOCSO’s IPS recipients. We analyzed IPS data from 2002–2014 to examine frequency each of benefits offered, such as Invalidity Pension, Survivors’ Pension, Constant Attendance Allowance, Rehabilitation Benefit and Funeral Benefit. The registered number of employers had increased to approximately 5% in 2013. This is because SOCSO officers all around Malaysia had been actively searching for employers who have yet to register to make contributions for their eligible employees. Additionally, the total number of IPS recipients had steadily increased since 2002 to 2014. On average, the total number of IPS recipients increased at a rate of 62% every year. This study suggested that a large part of the increase in IPS claims could be explained by population which active contributors, and the increase result from equalization of IPS services across the country. In addition, it seems that the claims of low and high care levels depend on different factors. The increase in IPS claims should be monitored carefully to identify underlying factors and to ensure sustainability of the funding system.